Pencitraan Politik Wakil Walikota Medan (AR) Pada Akun Instagram @BAR - Martial, Abdulah Alfath; Saprianur, Annisa; Hadian, Endi; Sofia, Natasya; Ananda, Rizki Ayu (Peneliti.net, 2024)
This study uses a qualitative study with a material accumulative system. Through the documentation method by collecting and viewing uploads from the Instagram account @bar. Image politics is common everyday language in print and electronic media. Indonesian people who follow the trend of the Instagram application display various daily activities via Instagram. The upload from this account started on November 28 2017, only getting 62 likes and 2 comments in 2020. On December 8 2022 this upload had 915 likes and several other uploads had up to 108 thousand viewers and received up to 8,385 thousand likes. This means that the political imagery on this account has received a lot of appreciation from netizens.